2014
DOI: 10.1152/ajplung.00164.2013
|View full text |Cite
|
Sign up to set email alerts
|

Newborn rat response to single vs. combined cGMP-dependent pulmonary vasodilators

Abstract: . Newborn rat response to single versus combined cGMP-dependent pulmonary vasodilators. Am J Physiol Lung Cell Mol Physiol 306: L207-L215, 2014. First published November 15, 2013 doi:10.1152/ajplung.00164.2013.-Inhaled nitric oxide (NO) and other cGMP-or cAMP-dependent pulmonary vasodilators are often used in combination for the treatment of the persistent pulmonary hypertension of the newborn syndrome. There is in vitro evidence to indicate that NO downregulate the pulmonary vascular response to cGMP-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Three stimulations, applied 10 min apart, were employed and averaged to determine the EFS-induced force increase. Force was normalized to the tissue cross-sectional area (length*diameter*2), as previously reported for vascular tissue (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…Three stimulations, applied 10 min apart, were employed and averaged to determine the EFS-induced force increase. Force was normalized to the tissue cross-sectional area (length*diameter*2), as previously reported for vascular tissue (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…In a different line, continued work on the inhibition of phosphodiesterase (PDE)5 by Park and coworkers (270) demonstrated that sildenafil modulation of the NO/cGMP pathway promoted alveolarization (assessed by L m ) in the background of hyperoxia. These data highlight PDE5 as a candidate druggable target to drive alveolarization, and this has stimulated additional studies on the interaction between different cGMP-or cAMP-dependent agonists in the pulmonary vasculature in newborn rats (96). Interestingly, working in adult mice, Czövek and coworkers (79) have demonstrated the utility of VIP to stimulate the NO pathway and preserve lung function and structure in the background of hyperoxia in adult rats.…”
Section: New Mediators and Modulators Of Impaired Alveolarizationmentioning
confidence: 99%
“…It is primarily marketed for the treatment of erectile dysfunction, but also for treating PHT in adults [ 16 ]. It enhances nitric oxide (NO)-mediated vasodilation [ 17 ], promotes pulmonary angiogenesis and decreases pulmonary arterial remodeling [ 18 , 19 ]. The drug is effective in children above 1 year of age who have PHT [ 20 ].…”
Section: Introductionmentioning
confidence: 99%